2013
DOI: 10.1111/dote.12130
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of esophagogastric junction distensibility measurement during Nissen fundoplication

Abstract: Increased esophagogastric junction distensibility has been implicated in the development of gastroesophageal reflux disease (GERD). Previous authors have demonstrated a reduction in distensibility following anti-reflux surgery, but the changes during the operation are not clear. Our study aimed to ascertain the feasibility of measuring intraoperative distensibility changes and to assess if this would have potential to modify the operation. Seventeen patients with GERD were managed in a standardized manner cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 18 publications
1
37
0
1
Order By: Relevance
“…Several studies demonstrated the feasibility of intra-operative FLIP use during fundoplication and a consistent reduction in EGJ-distensibility immediately following fundoplication 24, 25 . Reduction in EGJ-distensibility following transoral incisionless fundoplication (TIF) has also been reported 26, 27 .…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%
“…Several studies demonstrated the feasibility of intra-operative FLIP use during fundoplication and a consistent reduction in EGJ-distensibility immediately following fundoplication 24, 25 . Reduction in EGJ-distensibility following transoral incisionless fundoplication (TIF) has also been reported 26, 27 .…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%
“…This can be explained by the difference between distensibility and contractility of the lower oesophageal sphincter (LES). The EndoFLIP catheter has been used as “smart bougie” to gauge EGJ diameter during fundoplication [34] and peroral endoscopic myotomy [14, 35]. Recently it was shown that final intraoperative EGJ cross-sectional area inversely correlates with postoperative dysphagia assessed with the Eckardt score and determines gastroesophageal reflux in achalasia patients after peroral endoscopic myotomy or Heller myotomy [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…This may enhance surgical training and potentially improve surgical outcomes by guiding intraoperative modification of the wrap by providing real-time data on tightness of the wrap [34, 35]. As would be expected, EGJ distensibility measured intraoperatively with FLIP is less restricted after partial 270° Toupet compared to full 360° Nissen fundoplication [36].…”
Section: Impedance Planimetry and Functional Lumen Imaging Probementioning
confidence: 99%